Structural connection between gallium crystals and near-Tm liquids under ambient pressure. (15th January 2018) - Zhang, F.; Sun, Y.; Wang, X.D.; Cao, Q.P.; Jiang, J.Z.; Wang, C.Z.; Ho, K.M.
Abstract: We study the short-range structural order in liquid gallium prepared by ab initio molecular dynamics simulations. We found that at 400 K, which is close to the melting point (Tm) of Ga, the dominant motif in the liquid phase is identical to that in the stable solid phase Ga-I. Strong directional bonding in this motif prevents it from nucleation in the liquid phase. Meanwhile, a newly identified motif, topologically distinct from yet related to those in β-Ga and Ga-III phases, is also abundant in Ga liquid. This new motif could serve as precursors for β-Ga or Ga-III during crystallization. Graphical abstract: Image 1